2011
DOI: 10.1258/ht.2011.011012
|View full text |Cite
|
Sign up to set email alerts
|

Early return to work and improved range of motion with modified relative motion splinting: a retrospective comparison with immobilization splinting for zones V and VI extensor tendon repairs

Abstract: Introduction There is a lack of evidence on the best method for rehabilitating extensor tendon injuries in zones V and VI. The purpose of this study was to evaluate the outcomes of modified relative motion splinting compared with immobilization following repair of extensor tendons in zones V and VI. Methods A retrospective analysis compared the outcomes of relative motion splinting with immobilization. Sixteen patients (16 fingers) were treated by conventional immobilization splinting for four weeks (immobiliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
37
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 23 publications
1
37
0
Order By: Relevance
“…11,3032 Three studies investigated EAM using RMO compared to static or with no control group. 10,33,34 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…11,3032 Three studies investigated EAM using RMO compared to static or with no control group. 10,33,34 …”
Section: Resultsmentioning
confidence: 99%
“…911,21,30,31,34 The timing of return to work was not reported all studies, but in three studies investigating a specific EAM protocol – the immediate relative motion protocols (IRAM) using the RMO – patients returned to light duties at work around 3 weeks postoperative (3.2–3.9) compared to 9.4 weeks for static orthoses. 10,33,34 Only one study 28 (of 100 subjects) experienced tendon ruptures, with one in the EAM group and 2 in the dynamic extension orthosis group. Patient adherence was not consistently reported, and only three studies measured patient reported outcomes.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Risk of bias was assessed for all studies using published criteria for intervention studies (Higgins & Altman, 2008) and systematic reviews (Shea et al, 2007). The quality of included RCTs varied, with common problems being a lack of participant blinding, poorly described randomization methods, study dropout, and lack of longterm follow-up (Supplemental Table 2, online).…”
Section: Resultsmentioning
confidence: 99%